As religiões e a construção de um novo paradigma de conhecimento/Religions and the construction of a new paradigm of knowledge - Pfeffer, Renato Somberg (PLURA, Revista de Estudos de Religião / PLURA, Journal for the Study of Religion, 2015)
<!–[if gte mso 9]> 800x600 <![endif]–> O vigoroso progresso das últimas décadas fez estremecer as bases do paradigma científico moderno. O presente artigo defende que a ciência moderna não é a única ou a melhor forma de explicação possível da realidade. A metafísica, a religião, a arte ou a poesia podem ser tão válidas quanto a ciência. A religião, especificamente, pode ser uma protagonista na construção de um novo paradigma de conhecimento em uma sociedade secularizada. Abstract The strong progress of recent decades has shaken the foundations of the modern scientific paradigm. The article argues that modern science is not the only or best explanation of reality. Metaphysics, religion, art or poetry can be as valid as science. Religion, specifically, can be a protagonist in the construction of a new paradigm of knowledge in a secularized society. <!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman","serif"; –> <!–[endif] –>